Penggunaan Bobot Potong dan Bobot Karkas sebagai Penduga Yield Grade dan Luas Urat Daging Mata Rusuk Kambing Kacang - Pradana, Erbid Dwi; Muthalib, R. A.; Farizal, Farizal; Afzalani, Afzalani; Sulaksana, Indra; Hoesni, Fachroerrozi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the shape and closeness of the relationship between slaughter weight and carcass weight with yield grade and rib eye muscle area in kacang goats. The material used in the research was 30 male kacang goats at the Mat Beken livestock business with 15 age groups I2 (2 -2,5years), and 15 I3 (3 -3,5 years). The tools used are knives, machetes, ropes, "WeiHeng" hanging scales with a capacity of 50 kg with an accuracy of 0.01 kg, digital cake scales with a capacity of 10 kg with an accuracy of 0.001 kg, transparent plastic, grid paper, number label paper, latex gloves. , calipers with an accuracy of 0.01 mm and writing tools. The variables observed were slaughter weight, carcass weight, rib eye muscle area, fat depok percentage, back fat thickness. Data analysis was carried out using correlation and regression analysis. To determine the form of relationship between slaughter weight and carcass weight (Independent Variables) with yield grade and rib eye muscle area (Dependent Variables) in kacang goats. Multiple linear regression was used, while to determine the relationship between slaughter weight and carcass weight with yield grade and rib eye muscle area, simple linear regression was used. To determine the accuracy of the regression formula in estimating yield grade and rib eye muscle area, the deviation percentage is used. The results of a simple correlation analysis showed that there was a very significant relationship (P<0.01) between slaughter weight and yield grade and rib eye muscle area for I2-aged Kacang goats, while the age of I3-aged Kacang goats for slaughter weight and yield grade had a correlation. significant (P<0.05), there was a very significant relationship between carcass weight and yield grade and rib eye muscle area for I2 and I3 goat ages (P<0.01). The results of multiple analysis showed that slaughter weight and carcass weight with yield grade and rib muscle area for I2 and I3 age goats had a very significant relationship (P<0.01). Based on the results and discussion it could be concluded that slaughter weight and carcass weight can be used as an estimate of yield grade and rib muscle area of kacang goats.